Some Infections are Heritable or Endogenous: Biological and Mathematical Analysis - Salerian, Alen J (Advances in Social Sciences Research Journal, 2026)
This brief report presents biological and mathematical evidence to suggest some infections develop independent of contamination. The germ theory “infections result from invasions of human body by foreign microbes “has been the central paradigm for infectious disorders since Pasteur’s research in mid 1800’s. Tuberculosis ,leprosy, tinea versicolor H.Pylori infections are heritable and tetanus , pseudomonas aeruginosa burn wound infections , myasis and pinworm infections are endogenous. Conclusion: Some infections result from contamination whereas many others are inherited or develop internally consistent with Darwinian theory of evolution.: New species emerge from reproduction or evolution of more complex species from less complex ones.